Drying of Tangerine peel: kinetics and performance of a convective solar dryer (Research, Society and Development, 2020)
The development of new products and the waste reuse has been increasingly explored in different segments. Due to the high humidity of the fruit residues, they must be dried under controlled temperature conditions, to avoid the nutrients degradation. The use of solar energy to heat the drying gas can make the process environmentally sustainable and less costly. The aim of this work was to study the effect of ethanol on the drying kinetics of the tangerine peel, as well as to perform its convective drying using a box-type convective solar dryer. The effect of the initial mass of particles and the air speed on the drying efficiency and proximate composition of the flour of the fruit peel were evaluated. The results show that the kinetics could be represented by the Overhults model. The solar drying using the tray configuration obtained a good drying rate, reaching up to 74 ºC for 6 h of drying in a sunny day. The dry material was crushed to compose the tangerine peel flour, which had about of 60% fibers.